2008
DOI: 10.1093/ndt/gfm951
|View full text |Cite
|
Sign up to set email alerts
|

Chronic inflammation and mortality in haemodialysis: effect of different renal replacement therapies. Results from the RISCAVID study

Abstract: Data at 30 months from this study showed the synergic effect of CRP and pro-inflammatory cytokines as the strong predictors of all-cause and CV mortality. HDF was associated with an improved cumulative survival independent of the dialysis dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
131
0
13

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 199 publications
(158 citation statements)
references
References 29 publications
8
131
0
13
Order By: Relevance
“…[4][5][6][7] Several nonrandomized observational studies suggested a survival benefit in patients who are treated with online hemodiafiltration. [8][9][10][11] However, small randomized studies failed to show a difference between online hemodiafiltration and standard hemodialysis (as summarized by van der Weerd et al 12 ). On the basis of the above-mentioned theoretical considerations, the absence of conclusive clinical data, and the growing interest in convective techniques, the Convective Transport Study (CONTRAST) was initiated (ClinicalTrials.…”
mentioning
confidence: 99%
“…[4][5][6][7] Several nonrandomized observational studies suggested a survival benefit in patients who are treated with online hemodiafiltration. [8][9][10][11] However, small randomized studies failed to show a difference between online hemodiafiltration and standard hemodialysis (as summarized by van der Weerd et al 12 ). On the basis of the above-mentioned theoretical considerations, the absence of conclusive clinical data, and the growing interest in convective techniques, the Convective Transport Study (CONTRAST) was initiated (ClinicalTrials.…”
mentioning
confidence: 99%
“…Actually, lower predialysis ␤2M levels have been reported after 3 to 12 mo treatment with HDF, as compared with low-flux or high-flux HD (10)(11)(12)(13)(14)(15). It has been proposed that the improved survival of HDF patients, as reported in few observational studies (16)(17)(18), can be partly attributed to increased removal of ␤2M and other MMW uremic toxins by convective transport.…”
mentioning
confidence: 99%
“…1. Typically, convective diffusive procedures are characterized by an additional removal of hydrophobic middle molecules and protein (albumin) bound uremic toxins depending on the membrane characteristics (hydrophobic areas, pore size, adsorptive properties, biocompatibility) (Ahrenholz et al, 2004;Panicchi et al, 2008). The loss of protein bound substances leads to a membrane determined l o s s o f a l b u m i n d u ring olHDF sessions (Ahrenholz et al, 2004;Samtleben et al, 2003;Combarnous et al, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…However, none-biocompatible membranes and partly low flux hemodialysis increases proinflammatory cytokines such as TNF-alpha. Ultrapure dialysis fluid is of relevant importance to prevent inflammation (Panicchi et al, 2008). On the other hand complement activation plays a role for inflammation during the dialysis sessions therefore biocompatible membranes are urgently necessary (Hakim et al, 1984).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation